Malva sylvestris Flower Extract Exhibits Antineoplastic Potential Against Human Colon Cancer Cell Lines and Induces CDK2 Transcript Instability via Plant miR160-5p. - Villani, Valentina; Gismondi, Angelo (Nutrients, 2026)
Background: Malva sylvestris (the common mallow) is an herbaceous species widely used in ethnobotanical practices to treat gastrointestinal, hepatic and urinary inflammation. Objectives: Despite these beneficial effects on human health, the antineoplastic potential of this plant has not yet been fully explored. Thus, in the present study, two human colon cancer cell lines (i.e., HCT-116 and Caco-2) were treated with an extract obtained from M. sylvestris flowers (MFE), whose composition in terms of phytochemicals and microRNAs has been recently published by our research group, to explore its potential bioactivity. Methods/Results: MTT and Trypan blue assays demonstrated that MFE reduced tumour cell growth without causing significant cytotoxicity or apoptosis. Following the diphenylboric acid 2-aminoethyl ester-induced fluorescence of some plant metabolites, microscopy analysis proved that MFE components crossed the cell membranes, accumulating into nuclei. Wound assay and transwell tests documented that MFE was also able to reduce cell motility and invasiveness. In both cell lines qPCR experiments demonstrated that MFE caused the over-expression of factors, like VIMENTIN and E-CADHERIN, which negatively influence epithelial–mesenchymal transition in colon cancers. However, the effects of MFE appeared to be time-, dose- and cell type-dependent. In fact, the treatment induced senescence in P53-null Caco-2 cells (i.e., ROS, β-galactosidase and P21WAF1/Cip1) and a premise of differentiation (i.e., P27Kip1) in P53-wild-type HCT-116 cells, also via the CDK2/c-MYC/AKT axis, justifying its antiproliferative property. In parallel, the transfection of tumour cells with pure synthetic miR160b-5p—a microRNA identified in M. sylvestris flowers and predicted to target the human CDK2 transcript—resulted in gene silencing, thereby suggesting its central role in mediating the cross-kingdom effects of MFE on the investigated cancer models. Conclusions: Overall, these findings open new perspectives on the common mallow as a source of potential antimetastatic compounds and on the possible use of its plant microRNAs in the development of gene therapies.